Genetically Different Isolates of the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis Induce Differential Responses to Stress in Cassava - Peña, Ricardo (Front Plant Sci, 2020)
Water scarcity negatively impacts global crop yields and climate change is expected to greatly increase the severity of future droughts. The use of arbuscular mycorrhizal fungi (AMF) can potentially mitigate the effects of water stress in plants. Cassava is a crop that feeds approximately 800 million people daily. Genetically different isolates of the AMF R. irregularis as well as their clonal progeny have both been shown to greatly alter cassava growth in field conditions. Given that cassava experiences seasonal drought in many of the regions in which it is cultivated, we evaluated whether intraspecific variation in R. irregularis differentially alters physiological responses of cassava to water stress. In a first experiment, conducted in field conditions in Western Kenya, cassava was inoculated with two genetically different R. irregularis isolates and their clonal progeny. All cassava plants exhibited physiological signs of stress during the dry period, but the largest differences occurred among plants inoculated with clonal progeny of each of the two parental fungal isolates. Because drought had not been experimentally manipulated in the field, we conducted a second experiment in the greenhouse where cassava was inoculated with two genetically different R. irregularis isolates and subjected to drought, followed by re-watering, to allow recovery. Physiological stress responses of cassava to drought differed significantly between plants inoculated with the two different fungi. However, plants that experienced higher drought stress also recovered at a faster rate following re-watering. We conclude that intraspecific genetic variability in AMF significantly influences cassava physiological responses during water stress. This highlights the potential of using naturally existing variation in AMF to improve cassava tolerance undergoing water stress. However, the fact that clonal progeny of an AMF isolate can differentially affect how cassava copes with natural drought stress in field conditions, highlights the necessity to understand additional factors, beyond genetic variation, which can account for such large differences in cassava responses to drought.